المعزولة من اصابات سريرية مختلفة لبعض المضادات الحيوية Pseudomonas aeruginosa مقاومة جرثومة - سناء مهدي عريبي (University of Thi-Qar Journal of Science, 2019)
This study was conducted for the isolation and identification of P.aeruginosa from different clinicalcases. The total number of samples were 129 sample wounds; burns; urinary tract ; chronic otitis mediainfections and were collected from and detection of their susceptibility for 15 antibiotic .The total number of isolated and confirmed P.aeruginosa were 38 out from 129 samples.The distribution of positive isolates were 12 from 38 cases otisit infections ; 8 from 19 samples ofburnes ; 10 from 50 samples of urin ;8 from 22 samples of wounds .All isolates show A highperecentage of resistance (100%) aginst penicillin and ampicillin .the lower resistance was registratedaginst Amikacin (30%), azthromycin (22%) ;ciprofloxacin (18%). According to the results our isolateswere in consistent with what is called Multi Drug Resistant P.aeruginosa ( MDRPA) .The results ofthis study show that sex ;age and proloned antimicrobial admistration were fundamental factoers inreasing the chance of infection .